2019
DOI: 10.3390/ijms20061274
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Green and Black Tea Polyphenols on BRCA2 Deficient Chinese Hamster Cells by Synthetic Lethality through PARP Inhibition

Abstract: Tea polyphenols are known antioxidants presenting health benefits due to their observed cellular activities. In this study, two tea polyphenols, epigallocatechin gallate, which is common in green tea, and theaflavin, which is common in black tea, were investigated for their PARP inhibitory activity and selective cytotoxicity to BRCA2 mutated cells. The observed cytotoxicity of these polyphenols to BRCA2 deficient cells is believed to be a result of PARP inhibition induced synthetic lethality. Chinese hamster V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The presence of polyphenolic structure in naringin is the principal reason for complementary and multiple binding to the target, which is also in collateral with plenty of literature. (Alqahtani et al 2019;Su et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of polyphenolic structure in naringin is the principal reason for complementary and multiple binding to the target, which is also in collateral with plenty of literature. (Alqahtani et al 2019;Su et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Tea polyphenols affect regulatory systems of cells and may produce an inhibitory effect on various stages of carcinogenesis: inflammatory processes, cell transformation, proliferation, apoptosis, metastasis, and invasion [ 107 , 137 , 138 , 139 , 140 ]. It was found that EGCG and TF cause synthetic lethality in BRCA2-deficient cells through a PARP-dependent mechanism [ 141 ]. EGCG inhibits PARP-1 more effectively than TF, which is probably due to the presence of a haloyl group.…”
Section: Polyphenols As Parp-1 Inhibitorsmentioning
confidence: 99%
“…Since EGCG is an inhibitor of PARP1 [ 16 ], we studied the effect of EGCG on the interaction of PARP1 with nucleosomes.…”
Section: Resultsmentioning
confidence: 99%
“…The modulation of gene expression with EGCG is not accompanied by genotoxicity [ 10 ], and is assumed to be associated with the inhibition of different transcription factors, DNA methyltransferase and class I histone deacetylases [ 9 , 11 , 12 ]. Nucleus-associated mechanisms of EGCG action include the poisoning of topoisomerases I and II and the inhibition of poly(ADPribose)polymerase 1 (PARP1) [ 9 , 13 , 14 , 15 , 16 ]. PARP1 is a sensor of DNA damage, and recruits DNA repair proteins to DNA lesions [ 17 ].…”
Section: Introductionmentioning
confidence: 99%